Container Handling Algorithms and Outbound Heavy Truck Movement Modeling for Seaport Container Transshipment Terminals - (:unkn) unknown (My University, 2012)
This research is divided into four main parts. The first part considers the basic block relocation problem (BRP) in which a set of shipping containers is retrieved using the minimum number of moves by a single gantry crane that handles cargo in the storage area in a container terminal. For this purpose a new algorithm called the look ahead algorithm has been created and tested. The look ahead algorithm is applicable under limited and unlimited stacking height conditions. The look ahead algorithm is compared to the existing algorithms in the literature. The experimental results show that the look ahead algorithm is more efficient than any other algorithm in the literature. The second part of this research considers an extension of the BRP called the block relocation problem with weights (BRP-W). The main goal is to minimize the total fuel consumption of the crane to retrieve all the containers in a bay and to minimize the movements of the heavy containers. The trolleying, hoisting, and lowering movements of the containers are explicitly considered in this part. The twelve parameters to quantify various preferences when moving individual containers are defined. Near-optimal values of the twelve parameters for different bay configurations are found using a genetic algorithm. The third part introduces a shipping cost model that can estimate the cost of shipping specific commodity groups using one freight transportation mode-trucking- from any origin to any destination inside the United States. The model can also be used to estimate general shipping costs for different economic sectors, with significant ramifications for public policy. The last part mimics heavy truck movements for shipping different kinds of containerized commodities between a container terminal and different facilities. The highly detailed cost model from part three is used to evaluate the effect of public policies on truckers' route choices. In particular, the influence of time, distance, and tolls on truckers' route selection is investigated. .